2019
DOI: 10.3390/antiox8060181
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Heme Oxygenase-1 in Cardiovascular and Kidney Disease

Abstract: Heme oxygenase (HO) plays an important role in the cardiovascular system. It is involved in many physiological and pathophysiological processes in all organs of the cardiovascular system. From the regulation of blood pressure and blood flow to the adaptive response to end-organ injury, HO plays a critical role in the ability of the cardiovascular system to respond and adapt to changes in homeostasis. There have been great advances in our understanding of the role of HO in the regulation of blood pressure and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 122 publications
0
15
1
Order By: Relevance
“…Present study, the 28-day administration of PN formula may not be sufficient to stimulate endogenous NO generation in IMI rats. It has been suggested that vascular NO preservation includes eNOS expression and activity and that the stability of NO is regulated by HO-1 expression [19].…”
Section: Discussionmentioning
confidence: 99%
“…Present study, the 28-day administration of PN formula may not be sufficient to stimulate endogenous NO generation in IMI rats. It has been suggested that vascular NO preservation includes eNOS expression and activity and that the stability of NO is regulated by HO-1 expression [19].…”
Section: Discussionmentioning
confidence: 99%
“…Detoxification enzymes (HO-1, NQO1, and GST), synthesized under Nrf2 supervision, are a great help for antioxidant defence, as they are responsible for the prevention of the participation of various xenobiotics and heme in free radical production [127,[247][248][249]. Importantly, Nrf2 was shown to restrict/prevent iron-or heme-mediated oxidative stress by affecting the expression of the FPN1, ferritin and HO-1 genes [250].…”
Section: Nad(p)h Quinone Oxidoreductase-1 Nqo1mentioning
confidence: 99%
“…HO-1 is the inducible isoform (HO-2 is the constitutive form) which plays a central role in maintaining beige-like adipose tissue and improves cardiovascular and liver function [27,28]. Hence, pharmacological agents that upregulate HO-1 expression have been used as a therapeutic approach for the treatment of obesity and its associated metabolic and cardiovascular diseases [27,29]. However, these interventions are not specific to adipose tissue in prevention of the inflammatory adipokines.…”
Section: Introductionmentioning
confidence: 99%